Bridge maintenance inspection and evaluation - White, Kenneth R. (Civil engineering, 1992)
"Second Edition examines in detail the process of evaluating bridge conditions and offers a thorough study of bridge types - their origins, elements, and failures. Bridge Maintenance Inspection and Evaluation, Second Edition presents new and expanded information on condition ratings, capacity evaluations, load factor analysis, and the American Association of State Highway and Transportation Officials (AASHTO) suggested guidelines. "